2006
DOI: 10.1007/s10067-006-0472-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decrease in the activity of collagenase in the femoral head in patients with hip osteoarthritis

Abstract: In the XML version of the online publication the family name of the second author was incorrectly given as Pczek. In fact, the correct family name is Pączek.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Knee OA accounts for over 80% of the diseases total burden and affects at least 19% of the U.S. population aged 45 or older . Risk factors for OA include age, obesity, trauma, genetics, muscle weakness, prior surgery, and repetitive use among others . Age and obesity are consistently correlated with the prevalence of OA, with one epidemiological study reporting that evidence of OA can be found in 44% and 42.6% of males and females over the age of 30, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Knee OA accounts for over 80% of the diseases total burden and affects at least 19% of the U.S. population aged 45 or older . Risk factors for OA include age, obesity, trauma, genetics, muscle weakness, prior surgery, and repetitive use among others . Age and obesity are consistently correlated with the prevalence of OA, with one epidemiological study reporting that evidence of OA can be found in 44% and 42.6% of males and females over the age of 30, respectively .…”
Section: Introductionmentioning
confidence: 99%